Efficient derivation of human trophoblast stem cells from primed pluripotent stem cells - Wei, Yanxing; Wang, Tianyu; Ma, Lishi; Zhang, Yanqi; Zhao, Yuan; Lye, Kathryn; Xiao, Lu; Chen, Chunlin; Wang, Zhijian; Ma, Yanlin; Zhou, Xiaohua; Sun, Fei; et al. (Science advances, 2021)
A simple and efficient strategy to generate human trophoblast stem cells is reported to aid investigations of early placentation. Human trophoblast stem cells (hTSCs) provide a valuable model to study placental development and function. While primary hTSCs have been derived from embryos/early placenta, and transdifferentiated hTSCs from naïve human pluripotent stem cells (hPSCs), the generation of hTSCs from primed PSCs is problematic. We report the successful generation of TSCs from primed hPSCs and show that BMP4 substantially enhances this process. TSCs derived from primed hPSCs are similar to blastocyst-derived hTSCs in terms of morphology, proliferation, differentiation potential, and gene expression. We define the chromatin accessibility dynamics and histone modifications (H3K4me3/H3K27me3) that specify hPSC-derived TSCs. Consistent with low density of H3K27me3 in primed hPSC-derived hTSCs, we show that knockout of H3K27 methyltransferases (EZH1/2) increases the efficiency of hTSC derivation from primed hPSCs. Efficient derivation of hTSCs from primed hPSCs provides a simple and powerful model to understand human trophoblast development, including the pathogenesis of trophoblast-related disorders, by generating disease-specific hTSCs.